PERAN TEKNOLOGI HANS (Head and Neck support) DALAM REVOLUSI KESELAMATAN PEMBALAP FORMULA 1 - Rivan Saghita Pratama; Indra Ramadhan; Avivah Zalzabilah; Kiki Revalyn Amelia (STKIP Subang, 2025)
This study aims to analyze the development and affectiveness of the Head and Neck Support (HANS) technology as a safety standard for Formula 1 drivers. The main focus of the research is to evaluate the extent of which the implementation of HANS technology can reduce the risk of fatal head and neck injuries among drivers, as well as to examine its integration wirh other safety devices. The research method used is a descriptive qualitative approach. The subjects of the study include FIa regulations, F1 accident reports, biomechanical data, and laboratory test result from official journals and documents. The research hypothesis suggest that the implementation of HANS can significantly reduce the level of head and neck injuries in highspeed crashes, and that this technology has become an integral part of modern racing safety systems capable of saving drivers lives.